ORE FIELDS OF VAYK: (REPUBLIC OF ARMENIA) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
Studies conducted in a region with a wide development of crypto structures and a geological and structural analysis of the results made it possible to identify patterns of localization of mineralization. This made it possible to explain the position of the ore fields, to outline them, to quantify the estimated resources. The application of a similar approach in other areas may increase the efficiency of geological exploration.
Keywords: faults; ring structures; ore-controlling structures; ore fields; deposits; forecast resources